Legal Complexities of Hybrid Threats in the Arctic Region - Al-Aridi, Alaa (Teisė, 2019)
This article will focus on the legal framework that applies to the Arctic ocean and highlight the legal grey areas that hybrid campaigns could invest in to violate international maritime law and law relating to the use of force.
Keywords: jus ad bellum; law of the sea; hybrid threats; Arctic region